Importance of Tricuspid Regurgitation Velocity Threshold in Risk Assessment of Pulmonary Hypertension-Long-Term Outcome of Patients Submitted to Aortic Valve Replacement - Garcia-Ribas, Cora; Ble, Mirea; Gómez, Miquel; Mas-Stachurska, Aleksandra; Farré-López, Núria; Cladellas, Mercè (Frontiers in Cardiovascular Medicine, 2021)
Background: The upper physiological threshold for tricuspid regurgitation velocity (TRV) of 2.8 m/s proposed by the Pulmonary Hypertension (PH) guidelines had been questioned. The aim of this study was to evaluate the prognostic significance of preoperative PH in patients with aortic stenosis, long-term after valve replacement, using two different TRV thresholds (2.55 and 2.8 m/s). Methods: Four hundred and forty four patients were included (mean age 73 ± 9 years; 55% male), with a median follow-up of 5.8 years (98% completed). Patients were divided into three PH probability groups according to guidelines (low, intermediate and high) for both thresholds (TRV ≤ 2.8 m/s and TRV ≤ 2.55 m/s), using right atrial area>18 cm2 and right ventricle/left ventricle ratio>1 as additional echocardiographic variables. Results: In patients with measurable TRV (n = 304), the low group mortality rate was 25% and 30%, respectively for 2.55 and 2.8 m/s TRV thresholds. The intermediate group with TRV > 2.55 m/s was an independent mortality risk factor (HR 2.04; 95% CI: 1.91 to 3.48, p = 0.01), in contrast to the intermediate group with TRV>2.8 m/s (HR 1.44; 95% CI: 0.89 to 2.32, p = 0.14). Both high probability groups were associated with an increased mortality risk, as compared to their respective low groups. When including all patients (with measurable and non-measurable TRV), both intermediate groups remained independently associated with an increased mortality risk: HR 1.62 (95% CI 1.11 to 2.35 p = 0.01) for the new cut-off point; and HR 1.43 (95% CI: 0.96 to 2.13, p = 0.07) for guidelines threshold. Conclusion: A TRV threshold of 2.55 m/s, together with right cavities measures, allowed a better risk assessment of patients with PH secondary to severe aortic stenosis, with or without tricuspid regurgitation.